Consiraints and refinement of radiative transfer model for bathymetric mapping from satellite remotely sensed data - Hashim, Mazlan; Ahmad, Samsudin (1989)
This paper examines the a customization of radioactive transfer model for correlating the reflectance to-depth of a typical turbid coastal water of Malaysia, hence enabling the bathymetric information be extracted from satellite remotely sensed data.